Formation of the Mechanism of Communication Management - Myruta Nataliia M.; Zhovnir Volodymyr A. (Problemi Ekonomiki)
The article defines the concept of «mechanism of communication management» and considers the approach to its formation. It is found that its formation is influenced by the type of leader, the corporate culture present in the organization and, therefore, the management style and form of management of the organization and communications. On the basis of the studies, the authors propose a scheme of the sequence of formation of the mechanism of communication management depending on the form of management: centralized or decentralized. The proposed scheme contains stages common to both forms of communication management, such as: defining the mission and strategic and operational goals of the organization, defining the objective of communication management, defining the functions of communication management, determining the composition of the subject of management – the necessary divisions to achieve the goal of communication management, empowering them, establishing a hierarchy between divisions, determining the form of communication management, as well as the stages of forming a communication management mechanism in various forms: in the centralized form – distribution of responsibility for the implementation of functions between divisions, establishing responsibilities and relationships between divisions, stimulating the staff; in the decentralized form – delegation of authority by the subject to the object of communication management, distribution of roles in the team-object of communication management, stimulation of staff, regulation of communication processes. In accordance with the forms of management, methodological support for the formation of the management mechanism is developed. It is proved that the mechanism of communication management in both centralized and decentralized forms differs in the following characteristics: conditions for the development and implementation of a managerial decision, principles of building a communication management mechanism, methods of staff management, indicators of staff stimulation, elements of the communication process, including the content of the message, senders of the message, receivers of the message, communication channels and means of information transmission. The direction of further research will be the formation of a mechanism for managing communications in health care institutions.